Examining the Effect of Servant Leadership, Employees Psychological Empowerment and Innovative Work Behavior on Project Success: Evidence from Construction Industry - Ali, Sabir; Khan, Sohrab; Saleem, Zahra (Pakistan Journal of Humanities and Social Sciences, 2023)
This research work aims to study the association between servant leadership (SL) and project success (PS). The study also examines the mediating role of employee innovative work behavior (IWB) and psychological empowerment (PE) in the relationship between SL and PS. Current study collected data from 350 construction industry professionals working on different construction projects in Pakistan. SPPS and SmartPls software were used to analyze the gathered data. The analysis result show that SL is positively related to PS. IWB and PE also significantly influenced the relationship between SL and PS. This research is one of the first attempts to examine the nexus between SL and PS through the mediating role of employ IWB and PE in the construction industry.